2019
DOI: 10.1002/adma.201904182
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest Hybrid Redox Materials Self‐Assembled from Polyoxometalates and Single‐Walled Carbon Nanotubes

Abstract: The development of next‐generation molecular‐electronic, electrocatalytic, and energy‐storage systems depends on the availability of robust materials in which molecular charge‐storage sites and conductive hosts are in intimate contact. It is shown here that electron transfer from single‐walled carbon nanotubes (SWNTs) to polyoxometalate (POM) clusters results in the spontaneous formation of host–guest POM@SWNT redox‐active hybrid materials. The SWNTs can conduct charge to and from the encapsulated guest molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 30 publications
10
102
3
2
Order By: Relevance
“…532 eV associated to hydroxyl groups (Figure S3d, SI). This suggests that GNF acts as an electron reservoir compensating for the loss of electrons in ceria, as observed previously for other metal compounds inside carbon nanotubes, 79,80 effectively restoring the Ce 4+ /Ce 3+ balance.…”
Section: Mechanistic Considerationssupporting
confidence: 77%
“…532 eV associated to hydroxyl groups (Figure S3d, SI). This suggests that GNF acts as an electron reservoir compensating for the loss of electrons in ceria, as observed previously for other metal compounds inside carbon nanotubes, 79,80 effectively restoring the Ce 4+ /Ce 3+ balance.…”
Section: Mechanistic Considerationssupporting
confidence: 77%
“…28,29 In addition, Newton and colleagues have demonstrated that internal integration of POMs into conductive carbon nanotubes leads to remarkable improvement and stabilization of their electrochemical performance. 30 Here, we propose an unprecedented top-down approach for the deposition of polyoxometalate-like metal oxo clusters on high-porosity carbon electrodes. The approach employs classical solution-stable Keggin polyoxomolybdates [H 3 PMo 12 O 40 ] (¼ PMo 12 ), which combine Brønsted-acidity, redox-activity and catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative approach, Walsh, Newton, Khlobystov, and co‐workers recently demonstrated the embedding of POMs inside electroactive carbon nanotubes. This ground‐breaking concept could in future be used to design composite electrode materials where the POM is electrically “wired” to a carbon support and leaching is virtually impossible [106] …”
Section: Outlook and Emerging Topicsmentioning
confidence: 99%